Discriminant profile of subjects with a history of domestic violence: The role of Early Maladaptive Schemas (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The current study is based on the Schema Therapy developed by Jeffrey Young and aims to describe a discriminative profile of individuals with a history of physical marital violence and from individuals that does not show history. The sample consisted of 341 participants. The instruments used were: Young Schema Questionnaire, Revised Conflict Tactics Scale and the Family Background Questionnaire. A discriminative function among individuals with a history of physical marital violence in the current relationship and individuals with no history violence were found (χ2 = 43.098, p = 0.045) by grouping the variables: mistrust/abuse schema, defectiveness/shame schema, dependence/incompetence schema, subjugation schema and social isolation schema towards the individuals with a history of marital violence. The individuals without a history of marital violence were characterized by greater functionality in the family of origin, characterized by the absence of father´s physical abuse, sexual abuse, maternal physical abuse, physical neglect , well as a style of adequate maternal decision,parental alliance, paternal and maternal psychological adjustment.
Keywords: couples; marital violence; early maladaptive schemas